PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA BERDASARKAN MOTIVASI KERJA PADA KARYAWAN ADMINISTRATIF DI UNIVERSITAS SEBELAS MARET SURAKARTA - Muhammad Cholil, Heru Purnomo & (Universitas Slamet Riyadi, 2010)
ABSTRACT The research aim is to give answers of problem that discussed, that is influence transformational (X1) and transactional (X2) leadership style, where is more dominant between two variables to job satisfaction (Y). Another aim is to know the influence X1 to Y and X2 to Y with motivation of achievement (X3), afiliation (X4), and powerfull (X5) as moderator variable. The resarch object is administration staff non structural with status civil government staff, with minimal job time is 2 years at 9 faculty in UNS scope. The sum of research object is 404 and taken 100 person as research sample, and taken with proportional simple random sampling technique. Variable X1 and X2 based to MLQ, X3, X4, and X5 based to RN Luser, and Y based to MSQ approach. Instrument of collecting data with questionare and scoring with likert scale 1 to 5. The validity test is find 1 item question at variable X2, and 2 item question at variable Y, invalid, and unused to reseach. The result of reliability test, point out that the 3 variables is reliable. The data analyze used the multiple linear regression and or interactive with t test, F test, and determination coefficient. More hipotesis to have proof, that is influence X1 Y bigger than X2. Another result that is X3, X4, and X5 as a partial, moderating influence X1 to Y. But, only X5 that moderating influence X2 to Y, and X3 and X3 nothing. The implication of the research is manager and middle manager must develop commitment to create job satisfaction of staff by increasing knowledge and application some concept and theories, so study result of staff motivation criticism and dinamism. Keywords: style leadership, transformational and transactional, motivation, achievement, affiliation and powerfull, job satisfaction.